Trends of Tourette Syndrome in children from 2011 to 2021: A bibliometric analysis - Yang, Cuiling; Zhang, Jie; Zhao, Qiong; Zhang, Jingjin; Zhou, Jiang; Wang, Li (Frontiers in Behavioral Neuroscience, 2022)
Objective: Analyze the research status of Tourette Syndrome (TS) in children by CiteSpace and determine the current research hotspots and frontiers. Method: We chose publications indexed in the Web of Science Core Collection (WoSCC) database for studies related to TS in children from 2011 to 2021. We built online cooperation maps of countries/regions, institutions, authors, journals, references, and keywords by CiteSpace, and identified hotspots and frontiers of study for children's TS. Results: A total of 1232 publications about TS in children were downloaded from the WoSCC. The USA (414) was the country with the highest rate of production, and University College London (87) was the institution that had the highest publication rate. Andrea Eugenio Cavanna was the most prolific author (39 papers). There was inactive cooperation between institutions, countries/regions, and authors. The Journal of European Child & Adolescent Psychiatry was the most active journal. Hot topics focused on epidemiology, comorbidities, deep brain stimulation, behavioral therapy, basal ganglia, pharmacological treatment, and risk factors of TS in children. Conclusions: According to the CiteSpace results, this study found that authors, countries/regions, and institutions were not actively working together. Current research hotspots mainly consist of epidemiology, comorbidities, deep brain stimulation, behavior therapy, and basal ganglia. The main research trends include comorbidities, pharmacological treatment, and risk factors. Therefore, international cooperation should be strengthened in the future, and it should be mindful of the psychiatric comorbidities of TS, the choice of intervention measures, and early warning of risk factors.